Comparison of the Effects of Task Oriented Balance Training Versus Blindfolded Balance Training in Patients with Parkinson’s Disease - Sudha, N.; V., Rajalaxmi (INTI International University, 2022)
Objectives: The purpose of this study was to find the efficacy of task oriented balance training and blindfold balance training to improve postural balance in patients with Parkinson’s disease. Materials and Methods: A comparative study was done with 20 samples. The study was conducted in kriston clinic. The duration of treatment was 8 weeks. Both male and female individuals with Parkinson’s disease in concern about falling, instability and balance problem, between the age group of 50-55 were included. PD with other neurologic diagnosis, severe impairments, cardiac problem, uncooperative are excluded. The measurements were taken using Unified Parkinson’s Disease Rating Scale (UPDRS) and Berg balance scale (BBS). Based on inclusion and exclusion criteria and outcome measures, 20 subjects with Parkinson disease (PD) were divided into two groups. Group A- 10 subjects were treated by using Blind folded balance training and Group B-10 subjects were treated by using Task Oriented balance training. Before the onset of treatment protocol, the technique was explained to the patients and informed concern was taken from the patients. The baseline measurements were taken by using Unified Parkinson’s Disease Rating Scale (UPDRS) and Berg balance scale (BBS). The procedure was done by performing Blind folded balance training for 4 times a week for 8 weeks for group A and Task Oriented balance training is performed for 4 times a week for 8 weeks for group B. After the study, pre and post test measurement were taken and compared using Unified Parkinson’s Disease Rating Scale (UPDRS) and Berg balance scale (BBS).The collected data were tabulated and analyzed using IBM SPSS VERSION 20.0 SOFTWARE. The collected data were analyzed and tabulated with the descriptive and inferential statistics. For the descriptive statistics, the mean and standard deviation were calculated and for the inferential statistics, the parametric variables were treated with t-test. The results were tabulated and the results were plotted accordingly. Results: On comparing pre test and post test values within the Group A and B on Unified Parkinson’s Disease Rating Scale (UPDRS) and Berg balance scale (BBS) shows significant difference in mean values at p< 0.005. Conclusions: This study concluded that blindfolded balance training is effective in improving Balance in Parkinson’s disease patients with balance impairment, when compared to task oriented balance training.